Children's honor choir. Junior high. Middle school choir. Men's honor choir. (Mark Custom Recording, 1996)
Resumen: Conferencia Nacional organizada por American Choral Directors Association en la que se presenta Children's honor choir. Junior high. Middle school choir. Men's honor choir